Epilepsy, neuroinflammation and cannabidiol What do we know thus far? - Pesántez Ríos, Gabriela; Perucca, Emilio; Striano, Pasquale; Caraballo, Roberto; Pesántez Ríos, Ximena; Pascual-Pascual, S. I.; Pesántez Cuesta, Galo (Frontiers in Pharmacology, 2026)
Epilepsy is a common neurological disorder associated with recurring seizures that in about one-third of individuals are resistant to conventional medications. Neuroinflammation and alterations in the endocannabinoid system are involved in epileptogenesis and represent attractive targets for therapeutic interventions. Randomized placebo-controlled trials have shown that cannabidiol (CBD), one of the main active principles found in the Cannabis plant, significantly reduces seizure frequency in patients with Lennox-Gastaut syndrome, Dravet syndrome, and tuberous sclerosis complex (TSC). The FDA’s approval of a purified formulation of CBD (Epidiolex®) in 2018 marks a significant advance in the management of patients affected by these disorders. This review is focused on the activity of CBD as a neuroinflammatory modulator and antiseizure agent. Experimental evidence from in vitro and in vivo studies indicates that CBD reduces neuronal excitability and seizure activity by a wide range of mechanisms including, but not limited to, modulation of endocannabinoid, adenosine, GPR55, and TRPV1 receptors. It has also been shown that CBD’s molecular actions trigger immunomodulatory effects and inhibit neuroinflammation through reduced concentrations of proinflammatory cytokines, chemokines, reactive oxygen species (ROS) and neurotoxic factors in microglia. We discuss the evidence for CBD’s effects on neuroinflammation, and their implications for inhibition of epileptogenesis and seizure activity. We highlight how further elucidation of CBD’s mechanisms of action, and particularly its effects on neuroinflammation, could lead to a more rational, targeted utilization of this compound, guided by assessment of biomarkers predictive of clinical response. Improved understanding of CBD’s immunomodulatory and anti-inflammatory effects could also facilitate the design of controlled studies to confirm the potential value of this compound in the treatment of types of epilepsy beyond those for which regulatory approval has been already obtained.